ИСЛОМИЙ ҚОИДАЛАРНИНГ БАДИИЙ ТАЛҚИНИ (Scientific journal of the Fergana State University, 2023)
This  article  is  devoted  to  analyse  poetic  comments  “Siroj-ul muslimin” of  Alisher  Navai . Moreover  given  the  history  of  creation,  period  and  atmosphere